The Influence of Organizational Culture and Competence on Employee Performance - Hamdana Hamdana; Arwin Malik (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2022)
This study aims to determine the simultaneous and partial influence of organizational culture and competence on employee performance at the Makassar City Communication and Information Service. The data were obtained from 87 respondents determined based on the slovin method. Furthermore, the data were analyzed using descriptive and multiple linear regression analyses. This research is a quantitative research type. The type of data used is primary data obtained by distributing questionnaires to all respondents. This study used descriptive statistical techniques and SPSS-assisted path analysis for data analysis. In addition to maintaining data quality, research uses validity, reliability, and classical assumption tests. The analysis results show that organizational culture, competence, and employee performance descriptively are well perceived. The results of multiple regression analysis show that corporate culture and competence have a positive and significant effect on the performance of the Makassar City Communication and Information Service employees both partially and simultaneously.